Hyperammonaemia‐induced skeletal muscle mitochondrial dysfunction results in cataplerosis and oxidative stress. (23rd October 2016) - Davuluri, Gangarao; Allawy, Allawy; Thapaliya, Samjhana; Rennison, Julie H.; Singh, Dharmvir; Kumar, Avinash; Sandlers, Yana; Van Wagoner, David R.; Flask, Chris A.; Hoppel, Charles; Kasumov, Takhar; Dasarathy, Srinivasan
Abstract : Key points: Hyperammonaemia occurs in hepatic, cardiac and pulmonary diseases with increased muscle concentration of ammonia. We found that ammonia results in reduced skeletal muscle mitochondrial respiration, electron transport chain complex I dysfunction, as well as lower NAD + /NADH ratio and ATP content. During hyperammonaemia, leak of electrons from complex III results in oxidative modification of proteins and lipids. Tricarboxylic acid cycle intermediates are decreased during hyperammonaemia, and providing a cell‐permeable ester of αKG reversed the lower TCA cycle intermediate concentrations and increased ATP content. Our observations have high clinical relevance given the potential for novel approaches to reverse skeletal muscle ammonia toxicity by targeting the TCA cycle intermediates and mitochondrial ROS. Abstract: Ammonia is a cytotoxic metabolite that is removed primarily by hepatic ureagenesis in humans. Hyperammonaemia occurs in advanced hepatic, cardiac and pulmonary disease, and in urea cycle enzyme deficiencies. Increased skeletal muscle ammonia uptake and metabolism are the major mechanism of non‐hepatic ammonia disposal. Non‐hepatic ammonia disposal occurs in the mitochondria via glutamate synthesis from α‐ketoglutarate resulting in cataplerosis. We show skeletal muscle mitochondrial dysfunction during hyperammonaemia in a comprehensive array of human, rodent and cellular models. ATP synthesis, oxygen consumption, generation of reactive oxygen species with oxidative stress, and tricarboxylic acid (TCA) cycle intermediates were quantified. ATP content was lower in the skeletal muscle from cirrhotic patients, hyperammonaemic portacaval anastomosis rat, and C2C12 myotubes compared to appropriate controls. Hyperammonaemia in C2C12 myotubes resulted in impaired intact cell respiration, reduced complex I/NADH oxidase activity and electron leak occurring at complex III of the electron transport chain. Consistently, lower NAD + /NADH ratio was observed during hyperammonaemia with reduced TCA cycle intermediates compared to controls. Generation of reactive oxygen species resulted in increased content of skeletal muscle carbonylated proteins and thiobarbituric acid reactive substances during hyperammonaemia. A cell‐permeable ester of α‐ketoglutarate reversed the low TCA cycle intermediates and ATP content in myotubes during hyperammonaemia. However, the mitochondrial antioxidant MitoTEMPO did not reverse the lower ATP content during hyperammonaemia. We provide for the first time evidence that skeletal muscle hyperammonaemia results in mitochondrial dysfunction and oxidative stress. Use of anaplerotic substrates to reverse ammonia‐induced mitochondrial dysfunction is a novel therapeutic approach. Key points: Hyperammonaemia occurs in hepatic, cardiac and pulmonary diseases with increased muscle concentration of ammonia. We found that ammonia results in reduced skeletal muscle mitochondrial respiration, electron transport chain complex I dysfunction, as well as lower NAD + /NADH ratio and ATP content. During hyperammonaemia, leak of electrons from complex III results in oxidative modification of proteins and lipids. Tricarboxylic acid cycle intermediates are decreased during hyperammonaemia, and providing a cell‐permeable ester of αKG reversed the lower TCA cycle intermediate concentrations and increased ATP content. Our observations have high clinical relevance given the potential for novel approaches to reverse skeletal muscle ammonia toxicity by targeting the TCA cycle intermediates and mitochondrial ROS.